2018
DOI: 10.1007/s11010-018-3320-1
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor gene (A/G) polymorphism rs1137101 and renal cell carcinoma

Abstract: Leptin plays an important role in carcinogenesis as leptin/leptin receptor signaling promotes the angiogenesis, proliferation, and inhibits epithelial cell apoptosis. Variants in the leptin receptor gene have potential associations with renal cell carcinoma (RCC). We aimed to investigate association of rs1137101 (A/G) polymorphism at LEPR gene with risk of RCC and patients survival. 123 individuals were classified into group I: 73 RCC patients and group II: 50 healthy controls. Genotyping of the Gln223Arg (A/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In the current study, we found that the GA and GA+AA genotypes of rs1137101 were associated with decreased breast cancer risk. Some previous case–control studies reported that the A allele of rs1137101 is a protective factor against cancer occurrence ( 26 , 40 , 41 ), which were consistent with our results, but some studies have shown the opposite results ( 42 , 43 ). The inconsistent results may be due to differences in race, genetic background, environment, or lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found that the GA and GA+AA genotypes of rs1137101 were associated with decreased breast cancer risk. Some previous case–control studies reported that the A allele of rs1137101 is a protective factor against cancer occurrence ( 26 , 40 , 41 ), which were consistent with our results, but some studies have shown the opposite results ( 42 , 43 ). The inconsistent results may be due to differences in race, genetic background, environment, or lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the involved patients in the early-onset psoriasis group should be approached differently as regards lifestyle recommendations. Further findings in certain populations—that besides obesity, rs1137101 has been linked to type 2 diabetes mellitus [ 46 ], various types of cancer such as endometrial [ 47 ], prostate [ 48 ], colorectal [ 49 ] and renal cell carcinoma [ 50 ] as well as to keloid formation [ 51 ], multiple sclerosis severity score [ 52 ], the outcome of renal transplantation [ 53 ] and to susceptibility to polycystic ovary syndrome [ 54 ]—suggests that sub-stratification and follow up of the involved individuals may also be a promising basis for prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the methylation, the presence of Gln223Arg (A/G) rs1137101 SNP was also found to affect the risk of RCC and patients’ survival [ 206 ]. The GG genotype is associated with more aggressive tumour behaviour and shorter survival compared with GA and AA genotypes.…”
Section: Mechanisms Linking Obesity With Cancersmentioning
confidence: 99%